Application of an unsteady flow simulation model in the Dan Hoai main irrigation canal - Nguyen Duy Binh; Loof, Rainer; Bogardi, Janos J.; Paudyal, Guna N.; Japanese Government (Bangkok : Asian Institute of Technology, 1988)
A computer model for the simu lation of canal operation was developed using the equations for unsteady flow in open channe l s. The model is applicable for any main irrigation canal composed of a series of channels separated by control structures and with several off takes along the canal. Water losses due to seepage along the canal were included in the model . The programming language us ed is FORTRAN, a language s uit able for most of the microcomputers. The main irrigation canal of the Dan Hoai Irrigation System (Vietnam) was us ed for simulation and verification. A comparison of data computed by the model to observed data indicated good agreement.
A thesis submitted in partial fulfilment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Irrigation -- Vietnam -- Dan Hoai; Irrigation -- Simulation methods